In vivo testing of novel nitric oxide-releasing nanoparticles for alleviating heart failure using the zebrafish embryo model - Maram, Hasan (2024)
Heart failure (HF) is a multifactorial, heterogeneous systemic disease that is considered one of the leading causes of death and morbidity worldwide. It is well-known that endothelial dysfunction (ED) plays an important role in cardiac disease etiology. A reduction in the bioavailability of nitric oxide (NO) in the bloodstream leads to vasoconstriction and ED. Many studies indicated diminishment of peripheral arteries vasodilation that is mediated by the endothelium in the of patients with chronic HF. With the advancement of nanomedicine, nanotechnology can provide adequate solutions for delivering exogenous NO with the aid of nanoparticles (NPs) to treat ED. The properties of superparamagnetic iron oxide nanoparticles (SPIONs) enable both passive and active delivery of drugs. This prompted us to investigate the efficacy of our newly-developed hydrogel nanoparticles (NO-RPs) for the delivery and sustained release of NO gas to alleviate cardiac failure and inflammation in the heart failure zebrafish model. The hydrogel NO-RPs incorporate SPIONS and NO precursor. The sustainend release of NO in the NO-RPs (4200 s), overcomes the problem of the short half life of NO in vivo which is expected to ameliorate the reduced NO bioavailabilty, and its consequences in endothelial and cardiac dysfunction. Zebrafish embryos were used as the animal model in this study to determine the effect of SPIONs-loaded NO-RPs on the cardiovascular system. Cardiac failure was induced in 24hpf embryos by exposure to aristolochic acid (AA)(0.25, 0.5 μM) for 8 h, followed by the SPIONs-loaded NO-RPs (0.25, 0.5 mg/ml) for 48 h, experimental groups included: control group which is healthy non treated zebrafish embryos, AA injured zebrafish embryos (HF) model,and NO-RP treated HF zebrafish embryos. Survival rate was assessed at 72hpf. Cardiac function was also evaluated by analyzing cardiac parameters including heartbeat, major blood vessels primordial cardinal vein and dorsal aorta (PCV &DA) diameter, blood flow velocity in PCV & DA vessels, cardiac output, and PCV & DA shear stresses. All cardiac parameters were analyzed with the aid of MicroZebraLab blood flow analysis software from Viewpoint. In addition, we studied the molecular effects of the developed NO-RPs on the mRNA expression of selected pro-inflammatory markers: IL-6, and Cox-2. Our findings demonstrated that the NO-RPs improved the survival rate in the heart failure zebrafish model and reversed heart failure by enhancing blood flow perfusion in Zebrafish embryos, significantly. In addition, RT-PCR results showed that the NO-RPs significantly reduced the expression of pro-inflammatory markers (lL-6&COX-2) in the heart failure zebrafish model. Our study confirmed that the developed SPIONs-loaded NO-RPs are effective tool to alleviate cardiac failure and inflammation in the HF zebrafish model.